Felling maturity criteria of beech stands in Slovakia - Petráš, Rudolf (Zbornik gozdarstva in lesarstva, 2010)
In this paper, we focus on the felling maturity of beech stands in Slovakia. From an economic point of view, felling maturity of stands depends on volume production, assortment composition at different stand ages, and costs of forest labour. The culmination of net value production serves as a prevailing criterion of felling maturity. Our analyses showed a modest decrease in felling costs after the stand age of 40 years. The mean value increment of beech stands was yield class dependent. The ages of stands when total mean increments culminated were, in comparison with volume production, older on average by 15 years for gross yield and by 28 years for net yield. The latter culminated between 105 and 150 years.
Keywords: bukov gozd; prirastek; sečnja; Slovaška